THE RELEVANCE OF HIGH SPIRITUALITY IN THE PERIOD OF GLOBAL CRISES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The root causes of any crisis, in general, stem from spirituality, spiritual crises. Therefore, to overcome all social crises in human life, it is necessary to develop spirituality and cultivate high spirituality in society. This indicates the importance of studying this issue within a separate topic.